COVID-19 zugzwang: Potential public health moves towards population (herd) immunity - Raj S. Bhopal (Elsevier, 2020)
COVID-19 is pandemic, and likely to become endemic, possibly returning with greater virulence. Outlining potential public health actions, including hygiene measures, social distancing and face masks, and realistic future advances, this paper focuses on the consequences of taking no public health action; the role of natural changes such as weather; the adverse public health consequences of lockdowns; testing for surveillance and research purposes; testing to identify cases and contacts, including the role of antibody tests; the public health value of treatments; mobilising people who have recovered; population (a synonym for herd) immunity through vaccination and through natural infection; involving the entire population; and the need for public debate. Until there is a vaccine, population immunity is going to occur only from infection. Allowing infection in those at very low risk while making it safer for them and wider society needs consideration but is currently taboo. About 40-50% population immunity is sufficient to suppress an infection with a reproduction number of about 1 or slightly more. Importantly, in children and young people COVID-19 is currently rarely fatal, roughly comparable with influenza. The balance between the damage caused by COVID-19 and that caused by lockdowns needs quantifying. Public debate, including on population immunity, informed by epidemiological data, is now urgent.